Motivasi Penggunaan Media Sosial di Kalangan Mahasiswa Gen-Z - Adiarsi, Gracia Rachmi; Putra, Aditya Eka; Raymond, Raymond (Jurnal Nomosleca, 2024)
In the digital age, Generation Z (Gen Z) is deeply engaged with technology. This study explores Gen Z's motivations for excessive internet use, focusing on social media. Interviews with eight students showed that social media is used mainly for entertainment, communication, and social interaction, with Instagram, TikTok, and WhatsApp being the most popular. The research highlights financial and time management challenges affecting academic productivity. It provides valuable insights for educators, policymakers, and mental health professionals to address the benefits and challenges of Gen Z's digital lives.